Pengujian Black Box Pada Aplikasi Access By KAI Menggunakan Teknik Equivalence Partitioning - Vita Maharani, Puja; Zahrotun Nazah, Vina; Sholiha, Maratus; Haikal, Alif (CV. Shofanah Media Berkah, 2024)
The Access by KAI application, is an application developed by PT Kereta Api Indonesia to make it easier to order train tickets online. To be able to ensure the application meets user needs and functions as expected, testing is carried out using the Black Box Testing method with the Equivalence Partitioning Technique. This test involves testing the main functions on the login page, personal data page, and train page. Alpha testing is done internally to detect and fix bugs. The alpha test results detect errors or bugs that occur in the personal data menu that require further improvement. This research shows that the Equivalence Partitioning method is effective in identifying errors and ensuring that the application functions properly in various situations.